Perubahan Sifat Kimia dan Pola Pelepasan Amonium dan Nitrat pada Ultisol Darmaga yang Diberi Pupuk Pelet Berbahan Dasar Lumpur Kolam Ikan: Chemical Properties Changes and Releasing Pattern of Ammonium and Nitrate on Ultisol Darmaga Fertilized by Fishpond Sediment-Based Pellet Fertilizer - Arief Hartono; Lilik Tri Indriyati; Putri Tria Santari; Neng Elin Novianti (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Fishpond sediment-based pellet fertilizer enriched with fishpond water and goat manure was made to decrease load of nitrate contamination in water bodies. The objective of this research was to evaluate the changes of some soil chemical properties and the releasing pattern of nitrogen (N)-ammonium (N-NH4+) and N-nitrate (N-NO3-) in Ultisol Darmaga which was fertilized by pellet fertilizer. The rate of pellet fertilizer which was applied to the soil was 6.10 g of pellets/300 g of soil or equivalent to 40.8 ton of pellets ha-1. This rate was based on the amount of N fertilizer for sweet corn that was 200 kg N ha-1. The pots were incubated in 1 week, 2 weeks, 3 weeks, 4 weeks, 5 weeks, 6 weeks, 7 weeks, 8 weeks, 10 weeks, and 15 weeks at field capacity condition. Soil analyses were conducted after the end of each incubation period. The results showed that in the end of incubation period, the application of pellet fertilizer increased soil pH, organic carbon, cation exchange capacity, exchangeable bases, N-NH4+, and N-NO3- and total available N which is the total amount of N-NH4+, and N-NO3- compared to those of control soil. As for the releasing pattern of N-NH4+ and N-NO3-, in the 1 week to 7 weeks of incubation N-NH4+ was dominant and decreased after that. The decrease of N-NH4+ was followed by the increase of N-NO3-. The N-NO3- was dominant from 8 weeks to 15 weeks of incubation. The results recommended that fishpond sediment-based pellet fertilizer improved the soil properties and provided available N.